THE IMPORTANCE OF EARLY DETECTION OF ANXIOUS AND DEPRESSIVE SYMPTOMS IN OLDER ADULTS IN PRIMARY HEALTH CARE - de Abreu, Rafaella Antunes Fiorotto; de Araújo, Lívia Cavalcante; Teixeira, Ana Luiza Silva; Tavares, Isabela Nunes; Escobar, Nayanne Deusdara; Resplande, Ianka Lustosa; Mayor, Marcela de Souza Sotto; de Paiva, Maykon Jhuly Martins (Seven Editora, 2026)
Considering the accelerated aging of the Brazilian population and the impact of mental disorders on older adults’ functionality and quality of life, early detection of anxious and depressive symptoms is essential in Primary Health Care. This study aimed to identify the prevalence of depressive symptoms among older adults assisted at a Primary Health Care Unit in Gurupi, Tocantins, Brazil, using the Geriatric Depression Scale (GDS). This is a cross-sectional, observational, quantitative study conducted with 24 older adults aged 65 to 84 years. Data were analyzed using descriptive and inferential statistics, adopting a 5% significance level. The overall prevalence of depressive symptoms was 45.8%, with a predominance of mild cases. No statistically significant associations were observed between sex or age and GDS scores. These findings reinforce the importance of standardized mental health screening tools in Primary Health Care to enable early identification and timely interventions. Systematic screening contributes to comprehensive care and prevention of disease progression. DOI: https://doi.org/10.56238/sevened2026.008-074